2017
DOI: 10.1103/physreve.96.042301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental colored noise in single-species population dynamics

Abstract: Variability on the external conditions has important consequences for the dynamics and organization of biological systems, and, in many cases, the characteristic timescale of environmental changes as well as their correlations play a fundamental role in the way living systems adapt and respond to it. A proper mathematical approach to understand population dynamic, thus, requires of approaches more refined than e.g. simple white-noise approximations. To shed further light onto this problem, in this paper we pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 71 publications
1
28
0
Order By: Relevance
“…In this case one expects an N-independent extinction time, as discussed in detail in Dean & Shnerb (2019). This distinction between positive and negative E½r was demonstrated explicitly in many studies of stochastic-logistic (and logistic-like) systems (Lande et al, 2003;Spanio et al, 2017;Wada et al, 2018;Yahalom & Shnerb, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…In this case one expects an N-independent extinction time, as discussed in detail in Dean & Shnerb (2019). This distinction between positive and negative E½r was demonstrated explicitly in many studies of stochastic-logistic (and logistic-like) systems (Lande et al, 2003;Spanio et al, 2017;Wada et al, 2018;Yahalom & Shnerb, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…Interactive effects between density and resource levels, or other environmental conditions that affect energetic demand, play large roles in a variety of ecological issues, including population regulation (Dennis & Otten, 2000;Fowler & Pease, 2010;Gamelon et al, 2017;Spanio, Hidalgo, & Munoz, 2017), pairwise species interactions (Dallalio, Brand, & Grant, 2017;Dunson & Travis, 1991), and theories for the role of competition in structuring multi-species assemblages (Grime & Pierce, 2012;Tilman, 1988). Interactive effects between density and resource levels, or other environmental conditions that affect energetic demand, play large roles in a variety of ecological issues, including population regulation (Dennis & Otten, 2000;Fowler & Pease, 2010;Gamelon et al, 2017;Spanio, Hidalgo, & Munoz, 2017), pairwise species interactions (Dallalio, Brand, & Grant, 2017;Dunson & Travis, 1991), and theories for the role of competition in structuring multi-species assemblages (Grime & Pierce, 2012;Tilman, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of whether these experiments under-or overestimated the relative importance of social density, they demonstrated that social density exerts a substantial, measurable effect on reproduction, independently of the effects food level. Interactive effects between density and resource levels, or other environmental conditions that affect energetic demand, play large roles in a variety of ecological issues, including population regulation (Dennis & Otten, 2000;Fowler & Pease, 2010;Gamelon et al, 2017;Spanio, Hidalgo, & Munoz, 2017), pairwise species interactions (Dallalio, Brand, & Grant, 2017;Dunson & Travis, 1991), and theories for the role of competition in structuring multi-species assemblages (Grime & Pierce, 2012;Tilman, 1988). The extent to which these interactions reflect changes in the balance between nutrient acquisition and metabolic demand has only just begun to be explored (Ghedini, White, & Marshall, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…where in each time window there is a preference for a randomly chosen species. Different works have recently analyzed this type of models, showing that time-dependent habitat preference greatly improves predictions of empirical ecological patterns with respect to purely neutral theories [31,[85][86][87]. In particular, it has been claimed that these models provides more realistic estimates of dynamical quantities, such as average species persistence times and distributions of species turnover [88], compared with their neutral counterparts.…”
Section: E Temporally-dependent Habitat Preferencesmentioning
confidence: 99%